Transcriptomic analysis of the response of Avena sativa to Bacillus amyloliquefaciens DGL1 - Yang, Xue; Xie, Yongli; Wang, Tian; Qiao, Youming; Li, Junxi; Wu, Lingling; Gao, Ying (Frontiers in Microbiology, 2024)
Introduction Bacillus amyloliquefaciens DGL1, isolated from the arid sandy areas in Dagler, Qinghai Province, China, promotes the growth of Avena sativa variety “Qing Yan 1”. Methods To elucidate the transcriptomic changes in the oat root system following interaction with DGL1 and to reveal the molecular mechanism by which DGL1 promotes oat growth, treatment and control groups of oat roots at 2, 4, 8, and 12 h after inoculation with a suspension of strain DGL1 were analyzed using Illumina high-throughput transcriptome sequencing technology. The differentially expressed genes were determined through Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses, and the metabolic pathways and key genes were analyzed. Results The results showed that 7874, 13,392, 13,169, and 19,026 differentially expressed genes were significantly enriched in the glycolysis/gluconeogenesis pathway, amino acid metabolism, nitrogen metabolism, plant hormone signal transduction, and other related metabolic pathways in the oat roots at 2, 4, 8, and 12 h after inoculation with a DGL1 suspension. The GO and KEGG enrichment analyses revealed that the genes encoding plasma membrane ATPase, phosphoglycerate kinase gene PGK, ammonium transporter protein gene AMT, cellulose synthase gene CSLF6, and growth hormone response family gene IAA18 were significantly upregulated. Discussion It is hypothesized that the pro-growth mechanism of strain DGL1 in oats is the result of the coordination of multiple pathways through the promotion of oat energy metabolism, phytohormone signaling, secondary metabolite synthesis, and amino acid metabolism.